Experiência de 65 anos no tratamento da acne e de 26 anos com isotretinoína oral - Sampaio, Sebastião de Almeida Prado (2008)
This special article is based on the contents of a lecture given by Sampaio and was written together with Bagatin. It is a summary of the authors experience treating various forms of acne before and after the introduction of oral isotretinoin, which revolutionized the management of the disease. Nowadays, this drug is considered the unique option to obtain a prolonged remission or cure of acne due to its action in all etiopathogenic factors involved in the disease. Therefore it should be prescribed in accordance to current recommendations, as well as for difficult cases, including those showing tendency to scars or serious psychological and social repercussions. Other topical and/or systemic therapeutic modalities should be considered in the initial approach and for mild and moderate cases.